2021
DOI: 10.1538/expanim.20-0114
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of ceftriaxone exposure during pregnancy on maternal gut and placental microbiota and its influence on maternal and offspring immunity in mice

Abstract: This study aimed to investigate the association between microbiota found in the maternal gut and placenta, and whether ceftriaxone exposure during pregnancy could alter these microbiota, and consequently affect the immunity of the mothers and their offspring. The microbiota in the feces and placenta of the dams were comprehensively analyzed using16S rRNA sequencing. Furthermore, viable bacteria in the placentas and blood of pups were also isolated by plate cultivation then taxonomically identified in detail by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…However, current population and animal experimental studies have suggested that the first microbial exposure of newborns may occur before birth, and this exposure may have a regulatory effect on the development of the newborn’s immune system ( Collado et al., 2016 ; Gomez de Agüero et al., 2016 ). Our previous study found microorganisms in the placenta and cultured live bacteria from the blood of the newborn mice and the placenta, further verifying that microbial contact with the newborn might exist before birth ( Cheng et al., 2021 ). The maternal microbiota is considered to be the largest source of the gut microbiota of newborns, whereas the microbes of the vagina, skin, and oral cavity account for only a small proportion of the newborn gut microbiota, suggesting that the maternal microbiota has an important effect on the early gut microbiota of the offspring ( Shao et al., 2019 ).…”
Section: Introductionmentioning
confidence: 57%
“…However, current population and animal experimental studies have suggested that the first microbial exposure of newborns may occur before birth, and this exposure may have a regulatory effect on the development of the newborn’s immune system ( Collado et al., 2016 ; Gomez de Agüero et al., 2016 ). Our previous study found microorganisms in the placenta and cultured live bacteria from the blood of the newborn mice and the placenta, further verifying that microbial contact with the newborn might exist before birth ( Cheng et al., 2021 ). The maternal microbiota is considered to be the largest source of the gut microbiota of newborns, whereas the microbes of the vagina, skin, and oral cavity account for only a small proportion of the newborn gut microbiota, suggesting that the maternal microbiota has an important effect on the early gut microbiota of the offspring ( Shao et al., 2019 ).…”
Section: Introductionmentioning
confidence: 57%
“…The egg white mainly plays a role in resisting bacterial invasion and provides nutrients to the embryo, which has been reported as necessary for the start of embryo development (Willems et al, 2014). Several studies have confirmed that certain functional proteins in eggs can influence hatchability (Muramatsu et al, 1990;Rehault-Godbert et al, 2014;Cheng et al, 2021). Other studies in mammals have demonstrated that microbiota from various maternal sites during pregnancy may potentially influence the health and passive immunity of offspring.…”
Section: Introductionmentioning
confidence: 99%
“…However, concerns have been raised about the availability of ceftriaxone. The ease of one-time oral administration of cefixime may justify the continued use of cefixime in certain settings 8,9 …”
mentioning
confidence: 99%
“…The ease of one-time oral administration of cefixime may justify the continued use of cefixime in certain settings. 8 , 9 …”
mentioning
confidence: 99%
See 1 more Smart Citation